Otimização locacional de novas unidades armazenadoras de grãos em Minas Gerais - Marlon Fernandes de Souza (2019)
Considered as one of the main bottlenecks in Brazilian infrastructure, the grain storage must to keep developing itself to support the advance of Brazilian agribusiness. Deficit in storage capacity and mispositioning of the storage network are two of the main problems. The definition of the location of grain storage facilities is an infrequent decision, but demand special attention considering the size of the investment and its importance in a logistics system. The literature shows increasing advances in the subject. Spatial Multicriteria Analysis (SMCA) allows the use of geographic intelligence to support decision making. The solution of complex mathematical models has become possible due to advances in computational processing capacity and simulation techniques. The objective of this work was to provide decision support tools to improve the location and allocation of new grain storage units in the state of Minas Gerais, Brazil. In order to do this, the dissertation was structured in four chapters: The first presents a contextualization on the theme, the second presents an analysis of the spatial distribution of the storage supply across the state, the third shows the steps of a suitability map construction for locating new storage units through a spatially explicit model, in the fourth and last chapter a spatial database, based on a topological road network, was developed to support a location-allocation model for storage facilities. The models were applied in Minas Gerais due to its importance both in agriculture and in the agribusiness logistics in Brazil. The research has an exploratory-explanatory nature and the methodology is applied. The results show that from the 853 investigated municipalities, 785 presented some level of storage deficit, however, large kernels of deficit were not observed. In the uncertainty analysis of the suitability map, the Southern/Southwestern Minas Gerais mesoregion presented the largest number of municipalities (86) with robust areas, of high suitability and low uncertainty, but in small areas scattered across the region. On the other hand, the Northwestern Minas Gerais mesoregion presented the largest extension of contiguous areas. The number of municipalities in the Northwest is small due to the large municipal territorial extensions, however it is the most suitable region for investments in storage in the state.